Statistical analysis in microbiology : statnotes - Armstrong, Richard A.; Hilton, Anthony C. (Wiley-Blackwell Publication, 2011)
Based on the highly successful STATNOTES articles published in Microbiologist by the Society for Applied Microbiology, this book presents the most useful statistical tests in a clear way by applying them to real experiments in microbiology, meeting the need for a book devoted to data analysis in the field